PERAN ORANG TUA DALAM MENDUKUNG PROSES PEMBELAJARAN ANAK USIA DINI DI BA BALEHARJO - Binti Mardhiyah; Agustiani, Happy (Tunas Siliwangi, 2025)
This study aims to determine the role of parents in supporting the learning process of early childhood in BA Baleharjo. The approach used is descriptive qualitative research with observation, interview, and documentation methods. The results of the study indicate that the active involvement of parents as learning companions at home greatly influences children's motivation and learning development. Parents act as directors, encouragers, and providers of a supportive learning environment. These findings emphasize the importance of collaboration between parents and teachers to create a fun and meaningful learning atmosphere for early childhood. The conclusion of this study indicates that parental involvement is an important factor in supporting the success of children's learning processes in PAUD institutions.